تجسيد المشاريع السياحية و الفندقية بين الواقع و المأمول: Embodiment tourism and hotel projects between reality and hopeful - سعيدة بودودة (Journal of North African Economies, 2025)
The development of tourism as a fundamental project in socio-economic development, within the 2030 master plan of tourism development framework, should consider more this tourism sector so that it becomes the most important pole in the Algerian economy based on five dynamics including a partnership program between the public and private sector. To realize this project, Algeria has put the emphasis on the development of the investment, which is the cornerstone of the national tourism strategy. To attract the investors, by identifying the tourist exposure areas, and the opening of the economy to national and foreign investors, several tax and legal advantages have been granted to the said investors to promote the realization of tourism investment projects. To revive the tourism sector it is necessary to create a pleasant environment for the investor, but despite the advantages offered for tourism development, Algeria has not been able to achieve the desired and hoped-for development in that sector.